URGENSI INFORMED CONSENT DALAM PENYELESAIAN SENGKETA MEDIS - Wijaya, I Made Adi Partha; Wedha, Yogi Yasa (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Informed consent in medical is a completeness, a necessity made by doctors before carrying out planned medical actions. The formulation of the problem in this study is how informed consent is regulated according to Indonesian law and why informed consent is important in medical dispute resolution. This research uses normative research methods with primary and secondary legal sources and uses statutory and conceptual approaches. The results showed that the regulation of informed consent according to Indonesian law is regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 290 / Menkes / Per / III / 2008 concerning Approval of Medical Actions and Law Number 17 of 2023 concerning Health. The position of informed consent in medical disputes functions doubly, namely from the doctor's side it is used as legal protection and a guarantee that the patient understands and agrees to the actions to be taken and from the patient's side as a manifestation of the right to self-determination which includes the right to obtain complete information about the benefits and risks of medical decisions taken.